Fabrication and characterization of yttria-stabilized zirconia solid electrolyte thin film via electrophoretic deposition - Garcia, Alexis Karla H.
Thin film solid electrolytes have been considered as one of the solutions in decreasing the contribution of ohmic resistance in a solid oxide electrochemical cell. The commonly used oxide-ion conducting solid electrolyte is 8 mol% Yttria-stabilized Zirconia (Y0.16Zr0.92O1.92) or 8YSZ due to its low cost, good chemical stability, and good ionic conductivity. However, fabrication of dense YSZ film via facile methods on porous electrode support is still a challenge. In this study, dense 8YSZ solid electrolyte film were fabricated on a porous Lanthanum Strontium Manganite-Yttria stabilized Zirconia (LSM-YSZ) composite pellet through electrophoretic deposition (EPD). Film thickness dependence was observed by varying the deposition time. Effect of sintering temperature (1200°C and 1300°C) and precursor powder treatment on the film's morphology and density were also reported. From SEM microstructural results, films with thickness of 1.5 to 9 µm were deposited on LSM-YSZ substrates. Precursor powder treatment such as ball milling and addition of dispersant reduced the particle size of the powders and subsequently produced denser films. In addition, the required sintering temperature to produce a dense film is reduced which suggests that sinterability of the films were improved by powder treatment. Morphology of the YSZ films from treated precursor powders are sintered at 1300°C were comparable to 1500°C-sintered bulk YSZ from untreated powders. Among the parameters used in this study, the optimal conditions to produce a dense YSZ film is by using ball milled YSZ powder with the addition of a dispersant and sintered at 1300°C. However, further investigation is needed to produce a 100% crack-free deposit using